The Type of Injury Dictates the Mode of Repair in Neonatal and Adult Heart. Issue 1 (12th May 2015) - Konfino, Tal; Landa, Natalie; Ben‐Mordechai, Tammy; Leor, Jonathan
Abstract : Background: The neonatal heart possesses the unique power to regenerate in response to resection of the left ventricular apex. We sought to determine whether the type of injury affects the mode of repair and regeneration. Methods and Results: Apical resection, or permanent left anterior descending coronary artery ligation, was induced in neonatal 1‐day‐old mice. Echocardiography was used to confirm and monitor cardiac injury and remodeling. Histological and immunohistochemical examinations of the resected and infarcted neonatal hearts revealed inflammation and granulation tissue formation. From day 3, early regeneration was identified at the injured sites and was characterized by dedifferentiation and proliferation of cardiomyocytes around the injured areas. The young cardiomyocytes infiltrated the granulation tissue and replaced it with a new myocardium. The ability of neonatal cardiomyocytes to proliferate was confirmed in neonatal heart organ cultures. Notably, myocardial infarction in neonatal mouse produced incomplete regeneration with a residual small infarct and, sometimes, aneurysm at 28 days after myocardial infarction. We then repeated the same experiments in the adult heart. Remarkably, myocardial infarction in the adult mouse heart produced a typical thin scar, whereas apical resection revealed an abnormal, epicardial, hemorrhagic scar 21 days after injury. Conclusions: Our findings suggest that the type of injury, resection, or infarction affects the mode of repair in both neonatal and adult mouse hearts. Identifying the differences in the mechanisms or repair of these 2 types of injuries could help to develop novel regenerative therapies relevant to human patients.